Membangun profil siswa berkebinekaan global melalui ajaran Tamansiswa Ngandel, Kandel, Kendel, dan Bandel - Qodri Jamalulail; Bonifatius Sigit Yuniharto; Heri Maria Zulfiati (Universitas Sarjanawiyata Tamansiswa, 2023)
Learning history for elementary school students through reading books is tedious. This study aims to describe the cultivation of global diversity student profiles through the implementation of Tamansiswa Ngandel, Kandel, Kendel, and wayward teachings. Research data were obtained through learning observation activities, student interviews, and documentation of learning outcomes. The subject of the study was a fifth-grade student of SDN Sariharjo for the 2021/2022 academic year. The research location is the Jogja Kembali monument. The implementation of Tamansiswa teachings is taken through a six-step group investigation (GI) type cooperative learning model, namely 1) identifying the discussion of the subject matter and grouping students; 2) arranging learning activities; 3) making observations and investigations; 4) complete the group report; 5) present a report on learning outcomes; and 6) evaluate students' understanding. The results showed that students enjoyed learning history through museum visits. Tamansiswa's teachings on Ngandel, Kandel, Kendel, and recalcitrant are seen when students experience firsthand the planning, investigation, and reporting activities of the investigation. The profile of students with global diversity is seen through which students can appreciate the history and location of historical relics near their school.